Implementation of EMASLIM Concept and Ki Hajar Dewantara’s Teaching in Accelerating Teacher Careers and Institutional Quality - Doni Uji Windiatmoko; Istiqlal Yul Fanani; Zelika Naswa Rimality; Apta Argyanti Salsabila (Jurnal Pendidikan Edutama, 2026)
Accelerating teacher careers and enhancing institutional quality require effective educational management and a strong philosophical foundation. The implementation of the EMASLIM concept (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator) combined with the educational philosophy of Ki Hajar Dewantara serves as a strategic framework to optimize madrasah management and teacher professional growth. This study aims to analyze how EMASLIM and Ki Hajar Dewantara’s teachings accelerate teacher careers and elevate the institutional quality of MI Muhammadiyah Gembong Purbalingga. Using a qualitative approach, data were gathered through questionnaires, direct interviews, and non-participatory observations involving the madrasah principal and teachers. The results demonstrate that integrating EMASLIM principles with Ki Hajar Dewantara's values significantly boosts teacher career development and overall institutional quality. The study concludes that combining structured educational management (EMASLIM) with humanistic pedagogical values (Ki Hajar Dewantara) creates a conducive environment for career advancement and institutional excellence in madrasahs. Teachers expressed their satisfaction with this combination, particularly in terms of career paths, teaching, and student learning support. Institutionally, this combination is an effective alternative to strengthen the vision and mission and demonstrate better change.